"RF-SoC": Integration Trends of On-Chip CMOS Power Amplifier: Benefits of External PA versus Integrated PA for Portable Wireless Communications. (14th March 2010) - Lie, D. Y. C.
Abstract : RFIC integration has seen dramatic progress since the early 1990s. For example, Si-based single-chip products for GSM, WLAN, Bluetooth, and DECT applications have become commercially available. However, RF power amplifiers (PAs) and switches tend to remain off-chip in the context of single-chip CMOS/BiCMOS transceiver ICs for handset applications. More recently, several WLAN/Bluetooth vendors have successfully integrated less demanding PAs onto the transceivers. This paper will focus on single-chip RF-system-on-a-chip (i.e., "RF-SoC") implementations that include a high-power PA. An analysis of all tradeoffs inherent to integrating higher power PAs is provided. The analysis includes the development cost, time-to-market, power efficiency, yield, reliability, and performance issues. Recent design trends on highly integrated CMOS WiFi transceivers in the literature will be briefly reviewed with emphasis on the RF-SoC product design tradeoffs impacted by the choice between integrated versus external PAs.